Magnetic solid‐phase extraction for determination of the total malachite green, gentian violet and leucomalachite green, leucogentian violet in aquaculture water by high‐performance liquid chromatography with fluorescence detection. Issue 12 (31st May 2016) - Zhao, Jiao; Wei, Daqiao; Yang, Yaling
Abstract : In this study, magnetic multi‐walled carbon nanotube nanoparticles were synthesized and used as the adsorbent for the sums of malachite green, gentian violet and leucomalachite green, leucogentian violet in aquaculture water samples followed by high performance liquid chromatography with fluorescence detection. This method was based on in situ reduction of chromic malachite green, gentian violet to colorless leucomalachite green, leucogentian violet with potassium borohydride, respectively. The obtained adsorbent combines the advantages of carbon nanotubes and Fe3 O4 nanoparticles in one material for separation and preconcentration of the reductive dyes in aqueous media. The structure and properties of the prepared nanoparticles were characterized by transmission and scanning electron microscopy, X‐ray diffraction, and Fourier‐transform infrared spectroscopy. The main parameters affecting the adsorption recoveries were investigated and optimized, including reducing agent concentration, type and amount of sorbent, sample pH, and eluting conditions. Under the optimum conditions, the limits of detection in this method were 0.22 and 0.09 ng/mL for malachite green and gentian violet, respectively. Product recoveries ranged from 87.0 to 92.8% with relative standard deviations from 4.6 to 5.9%. The results indicate that the sorbent is a suitable material for the removal and concentration of triphenylmethane dyes from polluted environmental samples.